Alcohol use disorder and depression as dual pathology. Case report - Barroso-Fontanals, Miguel Enrique; Serra-Bauzá, Noel de Jesús; Herrero-Díaz, Adriel; Ramos-Labrada, Endris (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
Introduction: The comorbidity of alcohol use disorder and depression—dual pathology—carries a high suicidal risk and poor prognosis. This case is unique due to its early onset after traumatic grief and the simultaneous presentation of severe dependence, major depression, and a suicide attempt. It contributes a dual therapeutic strategy combining detoxification, pharmacotherapy, and grief-focused psychotherapy, rarely described in our setting. Objective: To describe the diagnostic-therapeutic approach to a case of dual pathology (severe alcohol use disorder and major depressive episode) with suicidal risk. Case Presentation: A 27-year-old male patient with daily consumption of 750 mL of rum, anhedonia, guilt, insomnia, and active suicidal ideation, plus a suicide attempt 15 days earlier with alcohol and diazepam. The main patient concerns were inability to control drinking and a feeling of emptiness. Relevant findings included AUDIT 28/40, Hamilton scale indicating severe depression, and Beck Suicidal Ideation scale showing high risk. Main diagnoses were severe alcohol use disorder, severe major depressive episode without psychotic symptoms, and complicated grief. Interventions comprised involuntary hospitalization, sertraline 50 mg/day, naltrexone 50 mg/day, and cognitive-behavioral therapy. At three months the patient remained abstinent, with significant reduction of depressive symptoms and return to work. Conclusions: Dual pathology with suicidal risk requires concurrent and long-term management. An intervention centered on processing traumatic grief, with family and community support, offers the best chance for recovery and relapse prevention.